APLIKASI KOMPOS TKKS DAN CENDAWAN MIKORIZA ARBUSKULAR TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KACANG HIJAU (Vigna radiata L.) DI TANAH ULTISOL - Riski Caner; Zulfatri Zulfatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
This study aims to determine the interaction of the application of oil palm empty fruit bunches (OPEFB) compostand arbuscular mycorrhizal fungi (AMF) and the single factor of each treatment of growth and production of mung bean plants (Vigna radiata L.) in Ultisol soil. The study was conducted in the Experimental Garden of the Faculty of Agriculture, Riau University in April - July 2019. The Research was usedfactorial completely randomized design (CRD). The first factor is the dosage of OPEFB compost (0, 37.5 and 75 g per plant) and the second factor is the dosage of AMF (0, 5 and 10 g per plant). The parameters observed were plant height, number of productive branches, age of flowering, age of harvest, number of pods per plant, number of seeds per pod, percentage of pods per plant, weight of seeds per plant, weight of 100 seeds, percentage of effective root nodules and percentage of infected roots CMA. The data obtained were statistically analyzed using variance then the results obtained were followed by Duncan's test of 5% level. The results showed that there was an effect of interaction between OPEFB and CMA compost on the percentage of CMA infected roots, flowering age and harvest age. TKKS compost application with a dose of 75 g per plant can accelerate flowering and harvest age, increase plant height, number of productive branches, number of pods per plant, number of seeds per pod, seed weight per plant, percentage of effective root nodules and percentage of infected roots. Application of CMA dose of 10 g per plant can accelerate flowering and harvest age, increase plant height, number of productive branches, number of pods per plant, number of seeds per pod, weight of seeds per plant and percentage of roots infected with CMA. Keywords: mung bean, compost OPEFB, AMF, Ultisol